KORELASI INTENSITAS CAHAYA DENGAN KARAKTERISTIK SUARA AYAM PELUNG - Indrawati Yudha Asmara; Dani Garnida; Nena Hilmia (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Pelung chicken is one of the singing chickens in Indonesia. Genetic factors and environmental factors such as light intensity influence the crowing characteristics of Pelung chickens. This research aimed to determine the correlation between light intensity at different times and the characteristics of the crowing sound of Pelung chickens. The study used a survey method with purposive sampling techniques in Cianjur and Sukabumi Regencies. A total of 26 Pelung chickens were sampled to measure the duration, frequency, and volume of crowing. The data obtained were analyzed using Pearson and Spearman rho correlation tests. The research results show that light intensity has a significantly low correlation with duration (0,0249). At the same time, the frequency and volume of crowing do not correlate with light intensity with the respective correlation values being 0,016 and 0,124. Further research with a larger sample is needed to strengthen the research results. Another study needs to be carried out regarding the training aspect and its influence on the characteristics of the crowing sound of Pelung chickens.